Is desertification a problem in Hungary? - Kertész, Ádám (Acta Geographica Debrecina Landscape & Environment series, 2016)
The term of “desertification” refers to a land degradation processes of arid, semiarid and sub-humid areas. Although the concept originates from Sub-Saharan Africa, desertification threatens also the area of Hungary. The greatest desertification risk is in the central part of the country, in the Danube-Tisza Interfluve where drought has always been a huge problem for the local society. Aridification processes are mainly due to climate change. Temperature increase and precipitation decrease as well as the increase of the frequency and amplitude of extreme events contribute to the acceleration of desertification risk. Severe or moderate droughts occur in Hungary nearly every year. Drought frequency has increased, primarily in the last decades. Main findings of several research projects of MEDALUS II and III EU Framework projects (experiments on the effects of climate change on vegetation, soils and ground water level) are summarized in the paper.